2018
DOI: 10.1007/s11082-018-1530-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of P+-ZnTe back surface contact on photovoltaic performance of ZnTe based solar cells

Abstract: In order to improve photovoltaic performance of solar cells based on ZnTe thin films two device structures have been proposed and its photovoltaic parameters have been numerically simulated using Solar Cell Capacitance Simulator software. The first one is the ZnO/CdS/ZnTe conventional structure and the second one is the ZnO/CdS/ZnTe/P +-ZnTe structure with a P +-ZnTe layer inserted at the back surface of ZnTe active layer to produce a back surface field effect which could reduce back carrier recombination and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the placement of BSF between the absorber and rear electrode can minimize the absorber layer thickness, minimizing the PV cell's overall cost. 33,34 In this article, the photovoltaic performance parameters of the proposed (ITO/TiO 2 /MoS 2 /In 2 Te 3 ) MoS 2 -based thin-film heterojunction SC without and with BSF have been analyzed utilizing the SCAPS-1D simulator. The investigation of the influence of the thickness, carrier concentration, defect density, working temperature, band alignment, rear electrode, capacitance−voltage (C−V), and back surface recombination velocity (SRV) on SC output parameters has been performed for optimizing the device structure as well as to determine better photoconversion efficiency in a cost-effective way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the placement of BSF between the absorber and rear electrode can minimize the absorber layer thickness, minimizing the PV cell's overall cost. 33,34 In this article, the photovoltaic performance parameters of the proposed (ITO/TiO 2 /MoS 2 /In 2 Te 3 ) MoS 2 -based thin-film heterojunction SC without and with BSF have been analyzed utilizing the SCAPS-1D simulator. The investigation of the influence of the thickness, carrier concentration, defect density, working temperature, band alignment, rear electrode, capacitance−voltage (C−V), and back surface recombination velocity (SRV) on SC output parameters has been performed for optimizing the device structure as well as to determine better photoconversion efficiency in a cost-effective way.…”
Section: Introductionmentioning
confidence: 99%
“…The BSF layer has been developed in this study with 50 nm-thick indium telluride (In 2 Te 3 ) in the molybdenum disulfide (MoS 2 ) solar cell, because of its ability to accumulate holes more effectively as well as reduces electron–hole recombination. Furthermore, the placement of BSF between the absorber and rear electrode can minimize the absorber layer thickness, minimizing the PV cell’s overall cost. , …”
Section: Introductionmentioning
confidence: 99%
“…The CVC measurements in a temperature range of 30-100 °C showed that the current exhibits an exponential dependence on applied voltage in a region of up to 1.6 V (Fig. 3); it can be approximated by the following expression: (1) where I o is the reverse current of the p-n heterojunction, q is the electron charge (q = 1.6  10 19 C), k is the Boltzmann constant (k = 1.38  10 23 J deg), and T is the temperature (K), n-ideality factor. A graphical representation of this dependence is shown in Fig.…”
Section: Research Resultsmentioning
confidence: 99%
“…The best known thin-film heterojunction solar cells are those made of CdS/CdTe. However, the possibility of designing other pairs of heterojunction systems based on А 2 В 6 compounds and solar cells based on these systems, in particular, CdS/ZnTe, is of interest [1,[3][4][5][6][7]. The theoretically calculated model of a CdS/ZnTe junction [2,3] for an optimum ZnTe thickness of 2 m gives an efficiency value of 10%, an open-circuit voltage (U OC ) of 1.81 V, and a short-circuit current density (J SC ) of up to 7 mA/cm 2 at a current-voltage characteristic (CVC) fill factor of 78.84%.…”
Section: Introductionmentioning
confidence: 99%
“…The use of dual semiconductor materials of zinc telluride and cadmium telluride thin films is crucial in various significant scientific and technological applications, such as solar cells and electronic devices [1][2][3][4][5][6][7], light-emitting diodes [8], and photodetectors [9]. This significance is due to their electronic and optical properties, where the dual systems of CdTe and ZnTe have a wide direct bandgap that allows their application as absorbing layers in solar cells [10][11][12][13], and they are also characterized by their high absorption coefficient that reaches 10 5 cm −1 [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%